A rationale for unanimity in committees - Yves Breitmoser; Justin Valasek (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2017)
Existing theoretical and experimental studies have established that unanimity is a poor decision rule for promoting information aggregation. Despite this, unanimity is frequently used in committees making decisions on behalf of society. This paper shows that when committee members are exposed to "idiosyncratic" payoffs that condition on their individual vote, unanimity can facilitate truthful communication and optimal information aggregation. Theoretically, we show that since agents" votes are not always pivotal, majority rule suffers from a free-rider problem. Unanimity mitigates free-riding since responsibility for the committee's decision is equally distributed across all agents. We test our predictions in a controlled laboratory experiment. As predicted, if unanimity is required, subjects are more truthful, respond more to others' messages, and are ultimately more likely to make the optimal decision. Idiosyncratic payoffs such as a moral bias thus present a rationale for the widespread use of unanimous voting.
Keywords: D71; D72; C90; 330; committees; incomplete information; decision rules; cheap talk; information aggregation; laboratory experiment